2014
DOI: 10.1007/s00266-014-0291-9
|View full text |Cite
|
Sign up to set email alerts
|

Anthropometry of the Breast Region: How to Measure?

Abstract: This journal requires that authors assign a level of evidence to each article. For a full description of these Evidence-Based Medicine ratings, please refer to the Table of Contents or the online Instructions to Authors www.springer.com/00266 .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…In this way, the obtained measurements are closer to actual body dimensions. Quieregatto et al 5 found significant differences between measurement taken with a tape measure and those taken with a compass at the same landmarks in the breast region. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this way, the obtained measurements are closer to actual body dimensions. Quieregatto et al 5 found significant differences between measurement taken with a tape measure and those taken with a compass at the same landmarks in the breast region. …”
Section: Discussionmentioning
confidence: 99%
“…Direct anthropometry consists of linear measurements between anthropometric landmarks performed directly on the body of the patient. Quieregatto et al 5 compared direct breast anthropometric measurements taken with a tape measure with those taken using a compass. Digital or printed images are used in indirect anthropometry and measurements are made using graphic software.…”
Section: Introductionmentioning
confidence: 99%
“…These points were selected to standardize the measurement of breasts and to increase the reproducibility of the methods. It has been shown that there are limitations to the points that could possibly be used for measurements on photographs in the oblique position and profile 8 .…”
Section: Discussionmentioning
confidence: 99%
“…The smaller the number of pixels used in the group, the greater the color resolution of the image obtained, because a group with a smaller number of pixels will be used to color a given segment and may cause changes in image definition (Figure 3). point more proximal to the anterior axillary line (Ax), and a point corresponding to half the distance between the acromion and the lateral epicondyle, called the "midpoint of the humerus" (a 1/2), according to the study by Quieregatto et al 6,8,9 (Figure 4).…”
Section: Introductionmentioning
confidence: 99%
“…Quieregatto et al 11 found differences between the tape and compass measurements of volunteers evaluated by direct anthropometry.…”
Section: Introductionmentioning
confidence: 99%